2016
DOI: 10.1177/1941874416675796
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage and Long-Term Stroke Risk After Traumatic Brain Injury

Abstract: Our findings do not support a role of tSAH in mediating the association between TBI and protracted stroke risk. Further study is required to elucidate the mechanisms of long-term increased stroke risk after TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The 18 studies included 2,606,379 participants and were from the United States, 16 24 Taiwan, 25 31 Croatia, 32 and Denmark. 33 All were retrospective cohort studies and eight different data sources were used ( Table 1 ), most commonly the Taiwan National Health Insurance Research Database 16 18 , 20 , 21 , 31 and United States Medicare administrative claims data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 18 studies included 2,606,379 participants and were from the United States, 16 24 Taiwan, 25 31 Croatia, 32 and Denmark. 33 All were retrospective cohort studies and eight different data sources were used ( Table 1 ), most commonly the Taiwan National Health Insurance Research Database 16 18 , 20 , 21 , 31 and United States Medicare administrative claims data.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies explored stroke risk post-TBI compared to non-TBI controls ( Table 1 ). 19 , 26 29 , 31 Eight studies investigated the association of stroke risk post-TBI with specific exposures: antidepressants; 18 , 20 statins; 21 oral anticoagulants; 16 , 33 traumatic subarachnoid hemorrhage (tSAH); 23 acupuncture; 30 and insomnia. 25 Two studies reported frequency of stroke post-TBI without a comparator 22 , 32 and two studies compared stroke incidence pre- and post-TBI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between TBI and stroke early after injury is not surprising, but the mechanism underlying a persisting link has not been established. 81 Various other diseases associated with TBI have a significant influence on long-term outcomes including epilepsy, 20,21 neuroendocrine disorders, 24 and neuropsychiatric illness, particularly depression. 10 A detailed discussion of these conditions is beyond the scope of this Series paper.…”
Section: Stroke and Other Neurological Disorders After Tbimentioning
confidence: 99%
“…TBI has also been associated with an increased risk for mood disorders, metabolic syndrome, diabetes mellitus, and substance use [13, 46], all of which increase vascular risk. While the possibility that persistent trauma-associated changes in vascular anatomy, cerebrovascular regulation, coagulation, and metabolism may contribute to this risk, other factors beyond unmodifiable risk associated with aging require further research, as an accurate understanding of modifiable risk factors can help with stroke prevention for those who sustain a TBI [47, 48].…”
Section: Discussionmentioning
confidence: 99%